Midface-lift patient satisfaction: A 5-year follow-up study - Michele Pascali; Davide Quarato; Ilaria Bocchini; Valerio Cervelli (Indian Journal of Plastic Surgery, 2016)
Context: Several studies showed, from the clinical point of view, the advantages of the various techniques and surgical approaches to obtain facial rejuvenation. A few studies have highlighted the satisfaction or not of patients who underwent a traditional facelift; however, a long-term follow-up study measuring patient satisfaction with midface-lift surgery has not been published yet. Aims: The aim of this study is to measure individual patient satisfaction with the midface lift, to find out from each patient his/her level of satisfaction 1 and 5 years after the operation and to compare the results to assess the benefits of the surgery. Background: Several studies showed, from a clinical point of view, the advantages of the various techniques and surgical approaches to obtain facial rejuvenation; however, a long-term follow-up study measuring patient satisfaction with midface-lift surgery has not been published yet. Materials and Methods: Between January 2005 and January 2010, 163 patients underwent a midface lift. All patients were asked to complete a standardised survey 1 and 5 years after surgery, in order to measure outcomes among facial aesthetic patients. Statistical Analysis Used: The paired t-test. Results: All patients reported an improvement as a result of the midface lift. Statistically significant differences in judgement criteria were found for malar eminence and nasojugal groove. Almost all of the patients turned out to be completely satisfied with their appearance with the new look. Conclusions: Patients were extremely satisfied with their decision to undergo a midface lift and with the outcomes and quality of life following the procedure.